Case study: Wellness, tourism and small business development in a UK coastal resort: Public engagement in practice. (June 2017) - Page, Stephen J.; Hartwell, Heather; Johns, Nick; Fyall, Alan; Ladkin, Adele; Hemingway, Ann
Abstract: This article examines the scope of well-being as a focus for tourism and its potential as a tool for small business development, particularly the opportunities for tourism entrepreneurs in coastal resorts. The study reports an example of public engagement by a research team and the co-creation of research knowledge with businesses to assist in business development by adapting many existing features of tourist resorts and extending their offer to wider markets. The synergy between well-being and public health interests also brings potential benefits for the tourism workforce and the host community. The Case Study outlines how these ideas were tested in Bournemouth, a southern coastal resort in the UK, in a study ultimately intended to be adopted nationally and with more wide reaching implications for global development of the visitor economy. Local changes ascribed to the study are assessed and its wider potential is evaluated. Highlights: Discusses tourism, well-being and public engagement. Examines value of well-being for tourism business and local community. Action research study located in Bournemouth, UK.